The enhancement of mammographic images of breast cancer using median filtering (software development ) / Noor Saedah Selamat - Selamat, Noor Saedah (1996)
Development of computer graphics and image processing techniques are becoming increasingly common in many application areas related to scientific engineering and medical fields. To efficiently visualise any inherent structure or spatial relationship that may exist in the image data, a user must have the ability to enhance, manipulate and display the image data. In this project, the development of median filtering algorithm were used to improve the quality of mammography images, hence this image can be used to determined and to detect any abnormalities in the image. These algorithm are written in C code using BORLAND C++ in Windows environment , improvise the poor image to become a clear image using enhancement techniques. One effective use of median filters has been the reduction of high-frequency and impulsive noise in digital images without the extensive blurring and edge destruction associated with linear filters [5], In addition to the enhancement technique , the edge enhancement and detection using sobel and kirsh operators were used . The graphics files format used are PCX ( PC paintbrush file format) and BMP ( windows' bitmap ).